An epigenetic modifier enhances the generation of anti-phytopathogenic compounds from the endophytic fungus Chaetomium globosporum of Euphorbia humifusa. (November 2022) - Cai, Xiao-Ying; Li, Na; Li, Yong; Zhang, Rui-Jia; Lin, Ping; Liu, Ling; Ye, Hao-Yu; Wu, Wen-Shuang; Zhao, Min
Abstract: Endophytic fungi are striking resources rich in bioactive structures with agrochemical significance. In order to maximize the opportunity of search for bioactive compounds, chemical epigenetic manipulation was introduced to enhance the structural diversity of the fungal products, and an UPLC-ESIMS and bioassay-guided separation was used to detect novel bioactive metabolites. Consequently, four previously undescribed compounds including two cyclopentenones (globosporins A and B) and two monoterpenoid indole alkaloids (globosporines C and D), as well as three known compounds, were isolated from the endophytic fungus Chaetomium globosporum of Euphorbia humifusa by exposure to a DNA methyltransferase inhibitor 5-azacytidine. Their structures including the absolute configurations were elucidated by the analysis of NMR spectroscopic data, HRESIMS, and TD-DFT-ECD calculations. The indole alkaloids (globosporines C and D) showed antimicrobial activities against three phytopathogenic microbes ( Xanthomonas oryzae pv . oryzae, X. oryzae pv . oryzicola, and Pseudomonas syringae pv . lachrymans ) with MICs in the range of 14–72 μg/mL. Mostly, globosporine D was proved to be potently anti-phytopathogenic against X. oryzae pv . oryzae in vitro and in vivo, which suggested that it has the potential to be developed as a candidate for the prevention of rice bacterial leaf blight. This work provides an efficient and environmentally friendly approach for expanding fungal products with agricultural importance. Graphical abstract: Four previously undescribed compounds were isolated from the endophytic fungus Chaetomium globosporum of Euphorbia humifusa by exposure to a DNA methyltransferase inhibitor 5-azacytidine, and globosporine D (5 ) exhibited potential anti-phytopathogenic against X. oryzae pv . oryzae in vitro and in vivo. Image 1 Highlights: Chemical epigenetic manipulation enhanced the chemical diversity of C. globosporum. Five new compounds were isolated from C. globosporum by exposure to 5-azacytidine. The structures of new compounds were determined by spectroscopic analyses. The new compounds showed antimicrobial activities against phytopathogenic bacteria. Globosporine D showed protective efficacy against rice bacterial leaf blight in vivo.